Léxico culinario en el Libro de cuentas de cocina y repostería de la Casa de Arcos (1750) - Marta Torres Martínez (Cuadernos AISPI, 2022)
Léxico culinario en el Libro de cuentas de cocina y repostería de la Casa de Arcos (1750)